TINJAUAN IMPLEMENTASI MODEL TERINTEGRASI FOGARTY DALAM PEMBELAJARAN DI SEKOLAH DASAR - Putri, Arizkylia Yoka; Nani Mariana; Suryanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Learning in elementary schools is a crucial initial stage in the formation of the academic and social foundations of students, who are the main focus of applying Fogarty integrated models. This study aims to explore the implementation of Fogarty integrated learning models in the context of learning in elementary schools, with a focus on the theme